Needle case, sound instrument or something else? A worked and ornamented swan (Cygnus sp.) ulna from a Late Mesolithic male burial, Yuzhniy Oleniy Ostrov, Northwest Russia - Mannermaa, Kristiina; Rainio, Riitta (Quaternary International, 2021)
The focus of this article is an analysis of tubular bone items made by cutting off the epiphyses of large bird ulnae, such as those found in burials 67 and 69 at Late Mesolithic Yuzhniy Oleniy Ostrov (Lake Onega, Northwest Russia). The bone tube from grave 69 was studied systematically, and tested to determine whether it could have been used as a sound instrument. In order to do so, we made a replica of the object, and tested its functions as a flute and a reed pipe. More generally, we propose alternatives to conventional and somewhat unimaginative interpretations of tubular bone artefacts. We raise awareness of their possible acoustic dimension, and discuss the outlook, structure, function and uses of simple bone flutes, whistles and reed pipes, highlighting their most common role as decoy whistles or animal calls. Blown instruments should be kept in mind when looking for explanations of tubular bone artefacts. Sound tools, and especially decoy whistles or animal calls, were common and necessary implements used everywhere and throughout all time periods, especially among hunters and fowlers, and should be considered a basic part of the bone tool assemblage. Peer reviewed